Late Eocene to early Oligocene calcareous nannofossil biostratigraphy of the Cerro Colorado Formation, Austral basin, Argentina - Bedoya Agudelo, Erika Lorena; Concheyro, Andrea; Olivero, Eduardo Bernardo (Journal of South American Earth Sciences)
This paper documents calcareous nannofossil assemblages and the bioevents recorded in the Austral basin of Tierra del Fuego, Argentina. Fifty samples from the type section of the Cerro Colorado Formation were analyzed. Nannoflora is moderately preserved and indicates a late Eocene to early Oligocene age for sedimentary rocks of this formation. Biostratigraphic results are based on distribution patterns of calcareous nannofossils assemblages, permitting comparison with the Southern Ocean zonations and some correlations with standard schemes. Our biostratigraphic interpretation shows an almost complete stratigraphic section spanning from the Priabonian to Rupelian Stages and calcareous nannofossil Chiasmolithus oamaruensis to Blackites spinosus zones, or the low latitude zones of Martini NP18 to NP21. The oldest fossiliferous rocks from the type locality of the Cerro Colorado Formation contain Chiasmolithus oamaruensis indicating nannofossil Zone NP18. The Eocene/Oligocene boundary was placed between the last occurrence (LO) of Reticulofenestra oamaruensis and the increasing in abundance (IB) of Reticulofenestra daviesii. Samples taken from the top of the section belong to the Estancia María Cristina Beds have Cyclicargolithus abisectus. During the late middle to late Eocene a hiatus is suggested between the Cerro Colorado and Leticia formations evident by a 39 Ma detrital zircon age dating, and the first occurrence (FO) of Dictyococcites bisectus. Furthermore, the presence of C. abisectus in the Estancia María Cristina Beds suggests an unconformity with the underlying Cerro Colorado Formation as previously inferred by stratigraphic relationships. Fil: Bedoya Agudelo, Erika Lorena. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Concheyro, Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos ...